2020
DOI: 10.3389/fimmu.2020.565521
|View full text |Cite
|
Sign up to set email alerts
|

Neurological Damage by Coronaviruses: A Catastrophe in the Queue!

Abstract: Neurological disorders caused by neuroviral infections are an obvious pathogenic manifestation. However, non-neurotropic viruses or peripheral viral infections pose a considerable challenge as their neuropathological manifestations do not emerge because of primary infection. Their secondary or bystander pathologies develop much later, like a syndrome, during and after the recovery of patients from the primary disease. Massive inflammation caused by peripheral viral infections can trigger multiple neurological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 139 publications
0
46
0
1
Order By: Relevance
“…CNS is potentially susceptible for this virus infection as reports clearly indicate COVID-19 patients suffering from neurological signs such as anosmia (loss of taste and smell), nausea, vomiting, headache and cerebral damages (stroke, encephalitis and degenerative symptoms) (13). Presence of SARS-CoV in brain tissues have also been reported before (14) and it is generally suggested that SARS-CoV-2 enters the brain by both route via hematogenous route as well as olfactory bulb through retrograde neuronal travel (10,15,16).…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…CNS is potentially susceptible for this virus infection as reports clearly indicate COVID-19 patients suffering from neurological signs such as anosmia (loss of taste and smell), nausea, vomiting, headache and cerebral damages (stroke, encephalitis and degenerative symptoms) (13). Presence of SARS-CoV in brain tissues have also been reported before (14) and it is generally suggested that SARS-CoV-2 enters the brain by both route via hematogenous route as well as olfactory bulb through retrograde neuronal travel (10,15,16).…”
Section: Introductionmentioning
confidence: 90%
“…Neurological damages by coronaviruses are now an established observation, supported by many experimental and clinical reports (10)(11)(12). CNS is potentially susceptible for this virus infection as reports clearly indicate COVID-19 patients suffering from neurological signs such as anosmia (loss of taste and smell), nausea, vomiting, headache and cerebral damages (stroke, encephalitis and degenerative symptoms) (13).…”
Section: Introductionmentioning
confidence: 95%
“…Immune cells infected with virus may attach to the brain endothelial cells and traverse across this layer and then come into contact with neurons. This may also occur with virus at the meningeal-cerebrospinal barrier and with virus present within blood vessels at the choroid plexus [13][14][15]. Infection with some neurotropic viruses has been reported to lead to encephalitis which can be fatal in some cases [6].…”
Section: Viral Infection Of the Cnsmentioning
confidence: 99%
“…However, it is still debated whether or not the virus directly infects the CNS. One study in this area of research did not report evidence of the presence of SARS-CoV-2 or its particles in the brain during the autopsy of patients with COVID-19, in spite of the viral invasion in various organs However, a first study did not report evidence of the presence of SARS-CoV-2 or its particles in the brain at autopsy of patients with COVID-19 infection in spite of the invasion of the virus in various organs such as lungs, liver and heart [ 47 ]. On the other hand, Moriguchi et al [ 48 ] observed viral RNA in the cerebrospinal fluid of a patient with aseptic encephalitis and Paniz-Mandolfi et al [ 49 ] reported the presence of SARS-CoV-2 viral particles in the neuronal and capillary endothelial cells in the frontal lobe tissue in a postmortem study.…”
Section: Pathogenesis Of Neuro-covidmentioning
confidence: 99%